Evaluation of energy consumption of corn agro-ecosystem associated with greenhouse gas emissions in semi-arid conditions - Hashempour, Nafiseh; Ardakani, Mohammad Reza; Damghani, Abdolmajid Mahdavi; Paknejad, Farzad; Ilkaei, Mohammad Nabi (Agriculture and Natural Resources, 2022)
Importance of the work: Extension innovation in up-scaling climate-resilient farming technology needs an integrated framework for existing mitigation options to reduce greenhouse gas (GHG) emissions in agricultural practices. Objectives: To investigate the energy dynamics and global warming potential (GWP) of corn grain and stover production systems in a corn field. Materials & Methods: The energy dynamics and GWP for corn grain and stover production systems were studied based on 2011–2016 Ministry of Agriculture statistical data in Iran per hectare of corn production system. Results: The amount of energy output in stover production was significantly higher, with a significant difference between observed renewable and non-renewable energies in the grain and stover production systems. Energy efficiency, energy productivity and net energy in the corn grain production system were significantly higher than from stover production, while the amount of specific energy in grain production significantly increased compared to the stover production system. Total GWP was 3,782.95 ± 1,088.28 kg CO2-eq/ha and 3,529.60 ± 970.77 kg CO2-eq/ha for the corn grain and stover production systems, respectively. In terms of CO2 equivalents approximately 22% and 23% of the GWPs came from CO2, 73% and 71% from N2O and 5% and 6% from CH4 for the corn grain and stover production systems, respectively. Therefore, the grain production system had the highest potential for global warming. For the grain and stover production systems, the GWP rates per unit weight were 0.56 ± 0.16 kg eq-CO2/ha and 0.04 ± 0.01 kg eq-CO2/ha, respectively, and per unit output energy were 0.20 ± 0.04 kg eq-CO2/ha and 0.05 ± 0.00 kg eq-CO2/ha, respectively, and per unite input energy were 0.16±0.04 kg eq-CO2/ha and 0.14±0.03 kg eq-CO2/ha, respectively. Main finding: Nitrogen fertilizer was the most important factor in GHG emissions from the corn grain and stover production systems. It is necessary to promote sustainable agro-ecosystems for the optimized use of production resources and reduced energy inputs and to reduce GWP in the agricultural sector, particularly regarding high-consumption inputs, such as fertilizers, seeds and irrigation water.